The Importance Of The Informatization Process In Improving The Quality Of Education - Ilkhomidin Rustamov, Phd (Periodica Journal, 2025)
This article analyzes the role of the informatization process in the modern educational system and its impact on the quality and effectiveness of Education. The implementation of information and communication technologies (ICT), the possibilities of improving the quality of the educational process through digital resources, interactive platforms and distance learning tools are considered. Also, the role of ICT in establishing effective communication between educators and students, current issues in the digitization of educational institutions, existing problems and ways to eliminate them are covered. The article concludes with scientific and practical recommendations aimed at modernizing education on an innovative basis.
Keywords: information; technology; informatization